Cloning, preparation and preliminary crystallographic studies of penicillin V acylase autoproteolytic processing mutants - Chandra, P. M.; Brannigan, James A.; Prabhune, Asmita; Pundle, A.; Turkenburg, J. P.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Cloning, purification, crystallization and preliminary structural studies of penicillin V acylase from Bacillus subtilis - Rathinaswamy, P.; Pundle, A. V.; Prabhune, Asmita; SivaRaman, H.; Brannigan, James A.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology Communications, 2005)
{Penicillin acylase proteins are amidohydrolase enzymes that cleave penicillins at the amide bond connecting the side chain to their beta-lactam nucleus. An unannotated protein from Bacillus subtilis has been expressed in Escherichia coli, purified and confirmed to possess penicillin V acylase activity. The protein was crystallized using the hanging-drop vapour-diffusion method from a solution containing 4 M sodium formate in 100 mM Tris-HCl buffer pH 8.2. Diffraction data were collected under cryogenic conditions to a spacing of 2.5 A. The crystals belonged to the orthorhombic space group C222(1), with unit-cell parameters a = 111.0

Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Bile salt hydrolase, the member of Ntn-hydrolase family: differential modes of structural and functional transitions during denaturation - Kumar, R. Suresh; Suresh, C. G.; Brannigan, James A.; Dodson, Guy G.; Gaikwad, Sushama M. (IUBMB Life, 2007)
Conformational transitions and functional stability of the bile salt hydrolase (BSH; cholylglycine EC: 3.5.1.24) from Bifidobacterium longum (BlBSH) cloned and expressed in E. coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and CD spectroscopy. Thermal and Gdn-HCl-mediated denaturation of BlBSH is a multistep process of inactivation and unfolding. The inactivation and unfolding of the enzyme was found to be irreversible. Enzyme activity seems sensitive to even minor conformational changes at the active site. Thermal denaturation as such did not result in any insoluble protein aggregates. However, on treating with 0.25-1 M Gdn-HCl the enzyme showed increasing aggregation at temperatures of 40-55 degrees C indicating more complex structural changes taking place in the presence of chemical denaturants. The enzyme secondary structure was still intact at acidic pH (pH 1-3). The perturbation in the tertiary structure at the acidic pH was detected through freshly formed solvent exposed hydrophobic patches on the enzyme. These changes could be due to the formation of an acid-induced molten globule-like state.
Keywords: Aggregation; Bile salt hydrolase; molten-globule; Unfolding

Purification and characterization of YxeI, a penicillin acylase from Bacillus subtilis - Rathinaswamy, Priya; Gaikwad, Sushama M.; Suresh, C. G.; Prabhune, Asmita; Brannigan, James A.; Dodson, Guy G.; Pundle, Archana V. (International Journal of Biological Macromolecules, 2012)
The paper reports the purification and characterization of the first penicillin acylase from Bacillus subtilis. YxeI, the protein annotated as hypothetical, coded by the gene yxeI in the open reading frame between iol and hut operons in B. subtilis was cloned and expressed in Eshcherichia coli, purified and characterized. The purified protein showed measurable penicillin acylase activity with penicillin V. The enzyme was a homotetramer of 148 kDa. The apparent Km of the enzyme for penicillin V and the synthetic substrate 2-nitro-5-(phenoxyacetamido)-benzoic acid was 40 mM and 0.63 mM, respectively, and the association constants were 8.93 x 10(2) M-1 and 2.51 x 10(5) M-1, respectively. It was inhibited by cephalosporins and conjugated bile salts, substrates of the closely related bile acid hydrolases. It had good sequence homology with other penicillin V acylases and conjugated bile acid hydrolases, members of the Ntn hydrolase family. The N-terminal nucleophile was a cysteine which is revealed by a simple removal of N-formyl-methionine. The activity of the protein was affected by high temperature, acidic pH and the presence of the denaturant guanidine hydrochloride. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bacillus subtilis; Conjugated bile acid hydrolases; Ntn hydrolase; Penicillin acylase

Cloning, overexpression, crystallization and preliminary X-ray crystallographic analysis of a slow-processing mutant of penicillin G acylase from Kluyvera citrophila - Varshney, Nishant Kumar; Ramasamy, Sureshkumar; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2013)
{Kluyvera citrophila penicillin G acylase (KcPGA) has recently attracted increased attention relative to the well studied and commonly used Escherichia coli PGA (EcPGA) because KcPGA is more resilient to harsh conditions and is easier to immobilize for the industrial hydrolysis of natural penicillins to generate the 6-aminopenicillin (6-APA) nucleus, which is the starting material for semi-synthetic antibiotic production. Like other penicillin acylases, KcPGA is synthesized as a single-chain inactive pro-PGA, which upon autocatalytic processing becomes an active heterodimer of alpha and beta chains. Here, the cloning of the pac gene encoding KcPGA and the preparation of a slow-processing mutant precursor are reported. The purification, crystallization and preliminary X-ray analysis of crystals of this precursor protein are described. The protein crystallized in two different space groups, P1, with unit-cell parameters a = 54.0

Structure mediation in substrate binding and post-translational processing of penicillin acylases: Information from mutant structures of Kluyvera citrophila penicillin G acylase - Chand, Deepak; Varshney, NishantKumar; Ramasamy, Sureshkumar; Panigrahi, Priyabrata; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Protein Science, 2015)
Penicillin acylases are industrially important enzymes for the production of 6-APA, which is used extensively in the synthesis of secondary antibiotics. The enzyme translates into an inactive single chain precursor that subsequently gets processed by the removal of a spacer peptide connecting the chains of the mature active heterodimer. We have cloned the penicillin G acylase from Kluyvera citrophila (KcPGA) and prepared two mutants by site-directed mutagenesis. Replacement of N-terminal serine of the beta-subunit with cysteine (Ser beta 1Cys) resulted in a fully processed but inactive enzyme. The second mutant in which this serine is replaced by glycine (Ser beta 1Gly) remained in the unprocessed and inactive form. The crystals of both mutants belonged to space group P1 with four molecules in the asymmetric unit. The three-dimensional structures of these mutants were refined at resolutions 2.8 and 2.5 angstrom, respectively. Comparison of these structures with similar structures of Escherichia coli PGA (EcPGA) revealed various conformational changes that lead to autocatalytic processing and consequent removal of the spacer peptide. The large displacements of residues such as Arg168 and Arg477 toward the N-terminal cleavage site of the spacer peptide or the conformational changes of Arg145 and Phe146 near the active site in these structures suggested probable steps in the processing dynamics. A comparison between the structures of the processed Serb1Cys mutant and that of the processed form of EcPGA showed conformational differences in residues Arg alpha 145, Phe alpha 146, and Phe beta 24 at the substrate binding pocket. Three conformational transitions of Arg alpha 145 and Phe alpha 146 residues were seen when processed and unprocessed forms of KcPGA were compared with the substrate bound structure of EcPGA. Structure mediation in activity difference between KcPGA and EcPGA toward acyl homoserine lactone (AHL) is elucidated.
Keywords: acyl homoserine lactone; autocatalytic processing; conformational changes; KcPGA_Ser beta 1Cys; KcPGA_Ser beta 1Gly; Ntn hydrolase